How Should the Government Bring Small Firms into the Formal System? Experimental Evidence from Malawi - Campos, Francisco; Goldstein, Markus; McKenzie, David (World Bank, Washington, DC, 2018)
Developing country governments seek to reduce the pervasive informality of firms for multiple reasons: increasing the tax base, helping firms access formal markets and grow, increasing the rule of law, and as a means to obtain data that can be used for other government functions. However, there is debate as to the best approach for achieving these goals. This study conducted a randomized experiment in Malawi to test three alternatives: (a) assisting firms to obtain a business registration certificate that offers access to formal markets but imposes no tax obligations; (b) assisting firms to obtain business registration and tax registration; and (c) supplementing the assistance to obtain business registration with a bank information session intended to help firms utilize one of the key potential benefits of formalizing. The study finds incredibly high demand for obtaining a formal status that is separate from tax obligations, and very low take-up of tax registration. Business registration alone has no impact on access to formal markets or firm performance. However, coupling registration assistance with the bank information session increases the use of formal financial services, and results in increases in firm sales by 20 percent and profits by 15 percent. The results highlight the advantages of separating business and tax registration, but also the need to assist firms in benefiting from their new formal status.